2010
DOI: 10.1007/s10336-010-0623-8
|View full text |Cite
|
Sign up to set email alerts
|

Short-term response to the North Atlantic Oscillation but no long-term effects of climate change on the reproductive success of an alpine bird

Abstract: International audienceDeciphering the effects of climatic conditions on population dynamics is of major importance in understanding how organisms are likely to be affected by climate changes. Using data from broad-scale annual censuses between 1990 and 2007, we show that winter and summer North Atlantic Oscillations affect several breeding success indicators of the Black Grouse () in the French Alps. We did not find any trend in hen counts or breeding indexes over the study period. Surprisingly for a bird spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…In a study of the white-tailed ptarmigan, Wang et al (2002b) reported that the local climate had a stronger signature on the demography of the species than did a largescale climate index. The use of the NAO index, as in the study by Barnagaud et al (2011) investigating the effect of climate on the breeding success of black grouse Lyrurus tetrix in the French Alps, would likely have been more appropriate if Rock Ptarmigan breeding success had been recorded over a broader scale.…”
Section: Discussionmentioning
confidence: 98%
“…In a study of the white-tailed ptarmigan, Wang et al (2002b) reported that the local climate had a stronger signature on the demography of the species than did a largescale climate index. The use of the NAO index, as in the study by Barnagaud et al (2011) investigating the effect of climate on the breeding success of black grouse Lyrurus tetrix in the French Alps, would likely have been more appropriate if Rock Ptarmigan breeding success had been recorded over a broader scale.…”
Section: Discussionmentioning
confidence: 98%
“…The range of black grouse habitat is also larger and possibly provides more variation in, e.g., precipitation and thus climate refuges. Similarly, climate trends also failed to explain variation in black grouse reproduction in the French Alps (Barnagaud et al, 2010). Consequences of climate change are predicted to increase in severity with increasing latitude (Houghton et al, 2001) and species may not simply have latitudinal or altitudinal range-shifts to compensate for e.g.…”
Section: Climate Changementioning
confidence: 99%
“…Birds may profit from these phenological adjustments, as individuals breeding early often have larger clutch sizes or higher overall reproductive success than those breeding later (e.g., Hatchwell 1991;Winkler et al 2002). Indeed, measures of breeding success were positively related to temperatures on the breeding grounds in several European and North American birds (Barnagaud et al 2011;Mihoub et al 2012;Van Oudenhove et al 2014). However, increasingly warmer springs do not correspond to enhanced reproductive success in all bird species and populations (e.g., Winkler et al 2002;Ludwig et al 2006).…”
Section: Introductionmentioning
confidence: 99%